2021
DOI: 10.1016/j.ajpc.2021.100245
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cascade genetic testing for familial hypercholesterolemia in the United States: A simulation analysis

Abstract: Objective There is no coordinated cascade testing program for familial hypercholesterolemia (FH) in the U.S. We evaluated the contemporary cost-effectiveness of cascade genetic testing relatives of FH probands with a pathogenic variant. Methods A simulation model was created to simulate multiple family trees starting with progenitor individuals carrying a pathogenic variant for FH who were followed through several generations. This approach allowed us to examine a family tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The Center for Disease Control and Prevention recommends cascade testing for FH (the leading and actionable Tier condition), because early diagnosis can be aided by genetic testing, and implementation of ASCVD prevention measures can have a significant public health impact. Cascade testing for FH has been shown to be highly cost-effective in multiple populations ( Marang-van de Mheen et al, 2002 ; Ademi et al, 2013 ; Kerr et al, 2017 ; Knowles et al, 2017 ; Lázaro et al, 2017 ), including children ( Wald et al, 2016 ; Ademi et al, 2020 ; Jackson et al, 2021 ). A related approach is child-parent testing, following the detection of a child at immunization at 2 years old ( Wald et al, 2016 ).…”
Section: Incorporating Lp(a) In Screening For Fhmentioning
confidence: 99%
“…The Center for Disease Control and Prevention recommends cascade testing for FH (the leading and actionable Tier condition), because early diagnosis can be aided by genetic testing, and implementation of ASCVD prevention measures can have a significant public health impact. Cascade testing for FH has been shown to be highly cost-effective in multiple populations ( Marang-van de Mheen et al, 2002 ; Ademi et al, 2013 ; Kerr et al, 2017 ; Knowles et al, 2017 ; Lázaro et al, 2017 ), including children ( Wald et al, 2016 ; Ademi et al, 2020 ; Jackson et al, 2021 ). A related approach is child-parent testing, following the detection of a child at immunization at 2 years old ( Wald et al, 2016 ).…”
Section: Incorporating Lp(a) In Screening For Fhmentioning
confidence: 99%
“…3 In The increased prevalence of the disease confirms the need to find patients to reduce the risk of death from cardiovascular events, which is its first silent manifestation at a young age. 14,26…”
Section: Epidemiological Backgroundmentioning
confidence: 99%
“…13 A systematic review of financial evaluations for the detection and treatment of familial hypercholesterolemia has shown that screening of relatives with suspected FH is highly costeffective. 14 The current European high levels of undiagnosed people with FH and associated morbidity and mortality mean that the adoption of ongoing services will bring significant benefits to quality of life and survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) There is currently no systematic way of identifying new index FH cases in the general population, although cascade testing in families of affected individuals has been shown to be highly cost-effective in many countries. (5)(6)(7)(8) showed that measurement of LDL-C alone at age 9 may be insufficiently accurate in reliably distinguishing FH-variant carriers from those with an elevated cholesterol as a consequence diet and lifestyle factors, or carriage of a high burden of common cholesterol-raising alleles, and suggested adding a confirmatory targeted-sequencing step to reduce the number of false positive cases detected. (10) The increased availability of routine health checks in adults either through work-place schemes or local healthcare providers offers an opportunity to systematically identify adult carriers of FH-causing variants.…”
Section: Introductionmentioning
confidence: 99%